2006
DOI: 10.3998/ark.5550190.0008.409
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric sensing of anions by a neutral biphenyl based amide receptor

Abstract: A new colorimetric sensor for fluoride is described. Compound 1 shows an open structure and its behaviour is compared with that of two related closed compounds 2 and 3. In all cases, the red colour developed in the presence of fluoride can be related to deprotonation processes, however ligand 1 gives rise to a faster colour change than 2 or 3 because of its higher flexibility. Other halides as well as carboxylates have been studied and the stoichiometry and complexation constants for the corresponding ligands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Homoditopic biphenyl thiourea derivatives have been prepared to be used in carboxylate sensing. Experimentals carried out with these ligands have demonstrated that the conformation of the free ligand has a strong influence on both complex stoichiometry and geometry [ 113 , 114 ]. Several bis-coronands from biphenyl have been prepared and their complexing and sensing properties for alkaline, alkaline-earth and transition cations have been studied [ 115 ] and one of them demonstrated to be a selective fluorescent sensor for mercury [ 116 ].…”
Section: Materials and Technologies In Chemical And Biochemical Sensomentioning
confidence: 99%
“…Homoditopic biphenyl thiourea derivatives have been prepared to be used in carboxylate sensing. Experimentals carried out with these ligands have demonstrated that the conformation of the free ligand has a strong influence on both complex stoichiometry and geometry [ 113 , 114 ]. Several bis-coronands from biphenyl have been prepared and their complexing and sensing properties for alkaline, alkaline-earth and transition cations have been studied [ 115 ] and one of them demonstrated to be a selective fluorescent sensor for mercury [ 116 ].…”
Section: Materials and Technologies In Chemical And Biochemical Sensomentioning
confidence: 99%